The year Nick McGowan came to stay [compact disc, unabridged] - Sparrow, Rebecca, 1972- (Random House/Listening Library, 2008)
In her final year of high school in 1989, Australian teenager Rachel has her world turned upside down when the most popular (and disturbed) boy in school comes to live with her family for a semester.